The impact of self-management practices on entrepreneurial psychological states - Michael Goldsby; James Bishop; Elizabeth Goldsby; Christopher B. Neck; Christopher P. Neck (Administrative Sciences, 2021)
It is well-known that entrepreneurs lead extremely busy lives. While research literature reports the stressors of entrepreneurial careers, few empirical studies have examined the actual management of the demands that entrepreneurs face in their daily lives. In this paper, we conducted a study of 472 small business owners and tested hypotheses on the roles of three self-management practices - exercise, work overload, and attention to detail - on stress, security, and job satisfaction. Exercise, work overload, and attention to detail serve as three important self-management practices that are largely under the decision-making of the individual entrepreneur.
Keywords: 350; entrepreneurship; exercise; psychological states; self-management